Recent Progress in Synaptic Devices Paving the Way toward an Artificial Cogni‐Retina for Bionic and Machine Vision. (23rd May 2019) - Berco, Dan; Shenp Ang, Diing
Abstract : In article number 1900003, Dan Berco and Diing Shenp Ang review recent progress in artificial synaptic devices in light of a futuristic visual perception platform. A cogni‐retina ("thinking eye") has the potential to perform image recognition tasks within sub‐nanosecond delays whereas software AI algorithms require millions of cycles. It is based on an artificial neural network that captures images as an imprint directly onto an array by altering the bitwise synaptic weights. Image processing can be done by parallel feed forward through successive layers of the same network.